2017
DOI: 10.1021/acs.jpcc.7b08457
|View full text |Cite
|
Sign up to set email alerts
|

Cycling Behavior of Silicon-Containing Graphite Electrodes, Part B: Effect of the Silicon Source

Abstract: Silicon (Si) is a promising candidate to enhance the specific charge of graphite electrode, but there is no consensus in the literature on its cycling mechanism. Our aim in this study was to understand Si electrochemical behavior in commercially viable graphite/Si electrodes. From the comparison of three types of commercial Si particles with a producer-declared particle sizes of 30–50 nm, 70–130, and 100 nm, respectively, we identified the presence of micrometric Si agglomerates and the Si micro- and mesoporos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…In fact, the application of a lower lithiation potential of 5 mV did not result in any signicant improvement despite the increased risk of lithium metal plating, while the complete lithiation also leads to a more severe volume expansion when forming the fully lithiated Li 15 Si 4 phase. 353 Aer an extrapolation of the expected capacity values for higher silicon contents, Schott et al 352 also studied electrodes with a ratio similar to that suggested previously by Yim et al 351 The resulting electrodes containing 10 wt% of silicon were able to compensate for the incomplete utilization of graphite when applying the higher cut-off potential of 50 mV, with silicon contributing with more than 50% to the total specic electrode capacity of ca. 650 mA h g À1 .…”
Section: Simentioning
confidence: 61%
“…In fact, the application of a lower lithiation potential of 5 mV did not result in any signicant improvement despite the increased risk of lithium metal plating, while the complete lithiation also leads to a more severe volume expansion when forming the fully lithiated Li 15 Si 4 phase. 353 Aer an extrapolation of the expected capacity values for higher silicon contents, Schott et al 352 also studied electrodes with a ratio similar to that suggested previously by Yim et al 351 The resulting electrodes containing 10 wt% of silicon were able to compensate for the incomplete utilization of graphite when applying the higher cut-off potential of 50 mV, with silicon contributing with more than 50% to the total specic electrode capacity of ca. 650 mA h g À1 .…”
Section: Simentioning
confidence: 61%
“…This deleterious volume change stimulated the development of Si nanomaterials, because Si at the nano scale can withstand swelling without fracture during LiB cycling. This has been demonstrated for a variety of morphologies including Si nanoparticles (SiNP) [ 6 , 7 , 8 , 9 , 10 , 11 ], Si nanowires (SiNW) [ 3 , 12 , 13 , 14 ], Si nanotubes [ 15 , 16 ], and Si porous nanomaterials [ 17 , 18 , 19 ]. However, nanostructuration can be a costly process that needs to be carefully optimized for a dedicated application.…”
Section: Introductionmentioning
confidence: 99%
“…A critical diameter was also predicted by a mechanical numerical model [ 23 ] at 90 nm for SiNPs and 70 nm for SiNWs. By contrast, several electrochemical studies in LiB investigated the impact of particle size on Si-based anode cycling for small [ 6 , 8 ] and large [ 7 , 8 , 9 ] SiNPs, with the best results at diameters of 20–50 nm. As for SiNWs, some studies have suggested the optimal diameter as being around 30 nm [ 10 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…As seen in the differential capacity curve, the Si−P1 also shows a small spike in accordance with this phase, as opposed to the amorphous nature of the Si−M1 and Si−P2, but this plateau fades with cycling. The formation of the Li 15 Si 4 phase in some Si particles and not others may arise from differences in the reaction kinetics during lithiation . Si particles can form a Li 15 Si 4 shell as the core slowly continues to lithiate.…”
Section: Figurementioning
confidence: 99%